Pediatric Cataract Surgery: Current Trends and Concepts - Khan, Muhammad Irfan (Pakistan Journal of Ophthalmology, 2016)
Cataract is an important factor in visual disability in children across the globe leading to significant deficiency in neurological milestones of a child. Pediatric cataract can affect three to six per 10,000 live births1 which accounts for approximately 200,000 children affected across the world. Congenital cataract presents in the first year of life while developmental cataract is seen after infancy or trauma. Factors such as onset age, laterality, cataract morphology, ocular associations and systemic diseases will decide the plan of management of a pediatric cataract.